“We Simply Laughed at the Concentration Camps”: Professor Jiří Franěk (formerly Frischman) Born in 1920 in Vysoké Mýto, died on Dec. 30, 2007, in Prague, Czechoslovakia - Dvořák, Jan (Lidé města, 2008)
June 27–30, 2004 recorded and transcribed (in Czech) by Jan Dvořák August 2008, translated into English and commented by František Franěk and Jacob Franek.